Penggunaan Asam Kresilat Topikal pada Lesi Kulit yang Aktif Berproliferasi - Wiwi Kertadjaja (Jurnal Kedokteran Meditek, 2018)
Cresylic acid is a common disinfectant used in hospitals. This study reported several cases where cresylic acid was used topically for the treatment of skin hyperkeratosis. Skin hyperkeratosis and plantar pedis caused by clavus were healed after application of cresylic acid for two weeks to two months. The patients did not require surgical removal of the lesion. The disease did not recur at the same location for a long period of time (one year). This may be due to antimicrobial activities of active agents in the cresylic acids such as phenol compounds or their derivates and benzalkonium chloride. However, application of cresylic acid for two weeks on a non-hyperplastic pigmentous nevus did not change the appearance of the lesion. The reported cases indicated that cresylic acid can be explored as an alternative for the treatment of skin hyperkeratosis.Keywords: Cresylic acid, active skin lesions